Synchronization of a camera and x-ray tube in digital radiography system in UNNES medical physical laboratory. (June 2020) - Susilo, S; Purwaningsih, P; Darsono, T; Dewi, A L; Taufiq, U A; Setiawan, R
Abstract: Much development of medical devices has been made in the field of radiology. An example is the development of analog radiology into digital radiology. The result of a digital radiographic x-ray is a digital radiograph that can be processed further with image processing techniques. After that it can be printed (printed image) or sent by a teleradiology method. To increase the digital image results, a delay was needed between the opening of the camera lens and the x-ray exposure. Then a delay circuit optimization is needed between the DSLR (digital single lens reflex) cameras, and x-ray exposure on Arduino Uno-based analog radiographs which are used as a unit delay and relay. In the unit delay, a push button triggered a millisecond, so that the Arduino IDE program was needed to set a delay. The relay functioned as a separator between the DC (Direct Current) on the camera and the AC (Alternating Current) on the x-ray tube. The results obtained were that the longer the x-ray exposure, the more intensity. Variation in delay time was regulated in the Arduino IDE program to get the best image quality with the least intensity of light to reduce radiation side effects in patients.